Developing consensus for upper limb rehabilitation, physical preparation and return to climbing in adults: protocol for an international e-Delphi study - Matthew Buckthorpe; Gareth Jones; Volker Rainer Schöffl; Stephen Patterson; Uzo Ehiogu (BMJ Open Sport & Exercise Medicine)
Climbing has grown into a grassroots participation sport and Olympic discipline. The high loads expressed through the upper limb may increase the risk of injury in this population. This may also affect rehabilitation and return to sport (RTS) considerations after injury. Treatment, management, rehabilitation and RTS parameters after injury are poorly documented. The aim of this study is to reach international expert consensus on the postinjury and surgical rehabilitation, physical preparation and RTS strategies in a range of climbers. This will provide a framework for the safe RTS of climbers. The study will be reported in accordance with guidance on conducting and reporting Delphi Studies guidelines. Panel members will be recruited with expertise in either the delivery of healthcare and/or physical preparation of climbers. The electronic Delphi is anticipated to consist of three irritative rounds. Round 1 will consist of open and closed questions to generate a broad range of statements on the rehabilitation, RTS and outcome measures used after climbing injury. In round 2, all participants will be provided with a summary of the current literature of the rehabilitation and RTS strategies for upper limb sports injuries. Rounds 2 and 3 will consist of a summary of the results from the previous round including any dissonance. Participants will be asked to anonymously rate responses on a 5-point Likert scale. The study steering group and patient public involvement representatives will be involved from conceptualisation until final dissemination.